2023
DOI: 10.3390/ijerph20206951
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Health Literacy and Public Health: A Machine Learning-Enhanced Bibliometric Investigation

Benjamin Tabak,
Matheus Froner,
Rafael Corrêa
et al.

Abstract: In recent decades, health literacy has garnered increasing attention alongside a variety of public health topics. This study aims to explore trends in this area through a bibliometric analysis. A Random Forest Model was utilized to identify keywords and other metadata that predict average citations in the field. To supplement this machine learning analysis, we have also implemented a bibliometric review of the corpus. Our findings reveal significant positive coefficients for the keywords “COVID-19” and “Male”,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Qualitative research already carried out, as mentioned in this article, has shown that healthcare professionals, policymakers, and telemedicine users await adequate regulation to ensure the safety of patients and physicians. See Silva et al [ 52 ] for a discussion on forecasting the pandemic and Tabak et al [ 53 ] for discussing health literacy and public health literature. Further research could explore how telemedicine helped reduce or limit contagion during the pandemic and the effects health literacy has on the effectiveness of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research already carried out, as mentioned in this article, has shown that healthcare professionals, policymakers, and telemedicine users await adequate regulation to ensure the safety of patients and physicians. See Silva et al [ 52 ] for a discussion on forecasting the pandemic and Tabak et al [ 53 ] for discussing health literacy and public health literature. Further research could explore how telemedicine helped reduce or limit contagion during the pandemic and the effects health literacy has on the effectiveness of telemedicine.…”
Section: Discussionmentioning
confidence: 99%